Long-Term Prognosis in Patients with Coronary Slow Flow - Amir Mikaeilvand; Reza Hajizadeh; Amin Bateni; Zhivar Yahyapour (Journal of Tehran University Heart Center, 2022)
Background: Coronary slow flow (CSF) is defined as decreased coronary blood circulation velocity and delayed opacification of contrast media during angiography. Evidence is insufficient regarding the course and prognosis of CSF patients. Long-term follow-up can help better understand the physiopathology and outcome of CSF. Accordingly, we assessed the long-term outcomes of CSF patients in this study.